THE CONTRIBUTION OF SOCIAL SCIENCES TO A CRITICAL READING OF THE MEDIA - Ferreira, Isabelle Azevedo; Silva, Lara Lanny de Oliveira; Alves, Rennata Kelly Muniz (Revista Inter-Legere, 2018)
Understanding that Social Sciences are challenged to provide theoretical and practical tools for the development of educational research, this article proposes to comprehend the role of Social Sciences and its cooperation to the area of media education. In a society increasingly dominated by the media, it is fundamental to understand how school, in this context, is responding to the challenges emerged by technology, that is transforming the ways in which society evolves and as it also questions the role of the media in the present time and its power to constitute reality. Using the thematic delimitation expressed in theses and dissertations as references, the specific objective is to verify the thematic and theoretical recurrences, the methodology used for it, as well as the difficulties encountered in the research on the ways in which the school institution and the teachers draw upon media and information and communication technologies (ICTs) to stimulate a critical analysis of the relation between the media and power. The analysis will be made based on the abstracts of the works defended in Brazil from 2005 to 2015, available in the database of Capes (Sucupira Platform) and in the Brazilian Digital Library of Theses and Dissertations (BDTD). The methodology used to analyze the abstracts will be through the analysis of the content. The proposed result points to a balance of researches already produced, as well as new possibilities of the intercultural exchange between fields of distinct traditions such as social sciences, communication and education. Keywords: Social Sciences. Communication. Education. Abstracts.